Isolation and identification of three species of bacteria from the termite coptotermes curvignathus (Holmgren) present in the vicinity of Universiti Putra Malaysia - Ramin, M.; Alimon, Abdul Razak; Abdullah, Norhani; Panandam, Jothi Malar; Sijam, Kamaruzaman (Academic Journals Inc., 2008)
In this study the lower termite Coptotermes curvignathus (Holmgren) and higher termite Macrotermes gilvus (Hagen) were identified from different parts in the vicinity of University Putra Malaysia (UPM). We isolated three enteric bacteria from the hindgut of Coptotermes curvignathus (Holmgren). All isolates were facultative anaerobes. The isolates were identified as Enterobacter aerogenes, Enterobacter cloacae and Clavibacter agropyri (Corynebacterium) by using BIOLOG assay and Bergey’s manual. The bacteria were able to assimilate carboxymethylcellulose (CMC) and cellobiose.